The prognostic significance of chromosome 17 abnormalities in patients with myelodysplastic syndrome treated with 5‐azacytidine: Results from the Hellenic 5‐azacytidine registry. (21st March 2019) - Diamantopoulos, Panagiotis; Koumbi, Dafni; Kotsianidis, Ioannis; Pappa, Vasiliki; Symeonidis, Argiris; Galanopoulos, Athanasios; Zikos, Panagiotis; Papadaki, Helen A.; Panayiotidis, Panayiotis; Dimou, Maria; Hatzimichael, Eleftheria; Vassilopoulos, George; et al.
Abstract: In patients with myelodysplastic syndrome (MDS), the prognostic significance of chromosome 17 abnormalities has not yet been fully elucidated, except for isochromosome 17q that has been characterized as an intermediate risk abnormality in the Revised International Prognostic Scoring System (IPSS‐R). To further characterize the prognostic significance of chromosome 17 abnormalities we analyzed the hematologic and prognostic characteristics of 548 adult patients with MDS treated with 5‐azacytidine through the Hellenic 5‐azacytidine registry and found 32 patients with a chromosome 17 abnormality (6 with i[17q], 15 with ‐17, 3 with add[17p] and the rest with other rarer abnormalities, mostly translocations). The presence of a chromosome 17 abnormality was correlated with poor prognostic features (high IPSS, IPSS‐R, and WPSS scores) and a low overall survival rate (15.7 vs 36.4 months for patients without chromosome 17 abnormalities, Kaplan–Meier, Log Rank P < 0.00001), but these results were confounded by the fact that most (92.3%) of the cases with a chromosome 17 abnormality (with the exception of i(17q) that was found in all cases as an isolated abnormality) were found in the context of a complex karyotype. Nevertheless, one should not ignore the contribution of chromosome 17 abnormalities to the prognostic significance of a complex karyotype since 33.8% of complex karyotypes encompassed a chromosome 17 abnormality. Abstract : To characterize the prognostic significance of chromosome 17 abnormalities we analyzed the hematologic and prognostic characteristics of 548 adult patients with MDS treated with 5‐azacytidine through the Hellenic 5‐azacytidine registry. The presence of a chromosome 17 abnormality (found in 32 patients) was correlated with poor prognostic features and a low overall survival rate. Although these results were confounded by the fact that most cases with a chromosome 17 abnormality were found in the context of a complex karyotype, one should not ignore the contribution of chromosome 17 abnormalities to the prognostic significance of a complex karyotype.